Енергоефективність технологічного процесу подрібнення зерна для комбікормів - Постнікова, Марина Вікторівна; Постникова, Марина Викторовна; Postnikova, Marina (ТДАТУ, 2020)
UK: У статті досліджувався технологічний процес подрібнення зерна для комбікормів молотковою дробаркою ДБ-5-1. При дослідженні вперше встановлені основні фактори, які впливають на величину питомих витрат електроенергії при подрібненні зерна для комбікормів, які є найбільш інформативним показником енергоефективності технологічного процесу подрібнення зерна. Вперше розроблений теоретичний метод перебудови математичної моделі молоткової дробарки, який оснований на використанні математичного апарату і методики класичної теорії планування експерименту. Теоретичні розрахунки підтвердили адекватність математичної моделі і ефективність використання методу багатофакторного математичного експерименту. Дослідження мають теоретичне і практичне значення і є основою для розробки науково-обґрунтованих норм електроспоживання технологічного процесу подрібнення зерна. RU: В статье исследовался технологический процесс измельчения зерна для комбикормов молотковой дробилкой ДБ-5-1. При исследовании впервые установлены основные факторы, влияющие на величину удельных затрат электроэнергии при измельчении зерна для комбикормов, которые являются наиболее информативным показателем энергоэффективности технологического процесса измельчения зерна. Впервые разработан теоретический метод перестройки математической модели молотковой дробилки, основанный на использовании математического аппарата и методики классической теории планирования эксперимента. Теоретические расчеты подтвердили адекватность математической модели и эффективность использования метода многофакторного математического эксперимента. Исследования имеют как теоретическое, так и практическое значение, и являются основой для разработки научно-обоснованных норм электропотребления технологического процесса измельчения зерна. EN: With the increase in energy tariffs, measures to improve the energy efficiency of agricultural facilities is becoming a priority for many owners of livestock farms. The economic situation in Ukraine is becoming a real stimulus for the introduction of modern technologies aimed at reducing the use of energy resources by agricultural enterprises. Substantiation of rational technological parameters of the technological process of grain grinding for compound feeds and rational energy parameters of crushers, which together increase the efficiency of compound feed preparation is an urgent scientific and applied task for the development of the livestock industry. The technological process of grain grinding for compound feeds with the hammer crusher DB-5-1 was investigated. The study identified the main factors that affect the amount of specific electricity consumption during grain grinding for feed, which is the most informative indicator of energy efficiency of the technological process of grain grinding. The influence of the main factors on the technological process was first established by means of a multifactor mathematical experiment. For the first time a theoretical method of reconstruction of the mathematical model of the hammer crusher was developed, which is based on the use of the mathematical apparatus and methods of the classical theory of experimental planning. This allowed us to obtain a regression equation to determine the specific consumption of electricity depending on the factors. Theoretical calculations confirmed the adequacy of the mathematical model and the effectiveness of the method of multifactor mathematical experiment. The accuracy of calculations is 3 %. Research has theoretical and practical significance, as it is the basis for the development of scientifically sound standards of electricity consumption of the technological process of grain grinding.
Энергоэффективность технологического процесса измельчения зерна для комбикормов
Energy efficiency of technological process of grinding grain for compound feed
Keywords: електропривод; економія електроенергії; енергоємність; багатофакторний експеримент; оптимізація питомих витрат електроенергії; электропривод; экономия электроэнергии; энергоемкость; многофакторный эксперимент; оптимизация удельных расходов электроэнергии; electric drive; energy saving; energy consumption; multifactor experiment; optimization of specific electricity consumption